Effect of corticosteroid injections versus physiotherapy on pain, shoulder range of motion and shoulder function in patients with subacromial impingement syndrome: A systematic review and meta-analysis - Marlette Burger; Carly Africa; Kara Droomer; Alexa Norman; Chloé Pheiffer; Anrich Gericke; Adeeb Samsodien; Natasha Miszewski (AOSIS, 2016)
Background: Subacromial impingement syndrome (SIS) is one of the most common causes of shoulder pain. Limited research has been conducted into the efficacy of corticosteroid injections (CSIs) compared to physiotherapy in the management of SIS. Objective: To critically appraise and establish the best available evidence for the effectiveness of CSI in comparison with physiotherapy for the management of pain, shoulder range of motion (ROM) and shoulder function in patients with SIS. Methodology:  Seven databases were searched from inception to February 2016, namely PubMed, Science Direct, EBSCO Host: SPORTDiscus, EBSCO Host: CINAHL, Cochrane, Scopus and PEDro. The main search terms were shoulder impingement syndrome and/or subacromial impingement syndrome, corticosteroid injections and/or steroid injections, physical therapy and/or physiotherapy. Only randomised controlled trials (RCTs) were considered for inclusion. The articles were appraised according to the PEDro scale. The Revman© Review Manager Software was used to combine the results of shoulder function and the data were illustrated in forest plots. Results: The PEDro scores of the three RCTs that qualified for this review ranged from 7 to 8/10. There is Level II evidence suggesting that besides a significant improvement in shoulder function in favour of CSI at 6-7 weeks follow-up (p < 0.0001), no evidence was found for the superiority of CSIs compared with physiotherapy for pain, ROM and shoulder function in the short- (1-3 months), mid- (6 months) and long term (12 months). Conclusion: In patients with SIS only a short term significant improvement in shoulder function was found in favour of CSIs.